Kesiapan Guru Terhadap Pemanfaatan Teknologi Asistif Untuk Siswa Dengan Hambatan Penglihatan: Sebuah Tinjauan Sistematis - Andi Dewangga Permana Putra (Peneliti.net, 2022)
This systematic literature review explores the readiness of teachers with students with visual impairments at all levels of education in terms of the use of assistive technology. Their readiness is seen from their perceptions, attitudes and self-confidence, and their skills in utilizing various assistive technologies for students with visual impairments. Thirteen studies were included in this review because they met the criteria. The results of the review indicate that teachers respond positively to the use of assistive technology. The level of teacher competency varies which has an impact on the effective use of technology. Emerging themes are discussed in more depth.